Menyelami perkembangan manusia : Buku 2 / Diane E. Papalia dan Ruth Duskin Feldman; Penerjemah, Fitriana Wuri Herarti - PAPALIA, Diane E.; FELDMAN, Ruth Duskin; FITRIANA Wuri Herarti; McGraw - Hill Education (Salemba Humanika, 2014)
xxiv, 318 (142) hlm. : ilus ; 28 cm.